Analisis Tingkat Produktifitas Tenaga Kerja Pada CV. Fajar Papua Abadi di Distrik Maribu Kabupaten Jayapura - Tanudy, Ayub (Jurnal Etnik: Ekonomi-Teknik, 2022)
CV Fajar Papua Abadi is a company that produces millstones and is located in the West Sentani District, Jayapura Regency. The type and source of data that the author uses in this writing is Primary Data which is data obtained directly from the source, namely CV Fajar Papua Abadi in West Sentani District, Jayapura Regency and secondary data is data obtained indirectly through books, magazines magazines and other guidebooks that can help writers in this research. Data collection methods used are observation, interviews and literature studies. The data analysis tool used in this paper is an analysis of labor productivity levels with the formula Labor Productivity = Output/Input x 100%. Based on the calculation results it can be explained that in 2018 a workforce of 10 people can produce 1,361 cubic millstones with a productivity level of 136.10%. In 2019 the number of workers increased to 12 people with millstone production of 1,472 cubic meters with a productivity of 122.66%. In 2020 the number of workers will increase to 14 people, able to produce 1,584 cubic millstones with a productivity rate of 113.14%. In 2021 the number of workers will increase to 15 people, able to produce 1,696 cubic meters of millstones with a productivity rate of 113.06%.